Comparative Study of Reduced Ripple DC-DC Converters for Various Applications - Rani, M. Devika; Lakshmi, V. Sai Geetha (International Journal of Computer Sciences and Engineering, 2025)
High-efficiency converters play an important role in the field of renewable energy, switch mode dc regulators, electric vehicles. Compared to linear voltage regulation switching conversion is more power efficient which dissipates unwanted power as heat. Switched mode converter due to its high efficiency reduces the heat sinking needed and increases battery endurance of portable equipment. Basically, DC-DC converters are designed to move unidirectionally, from input to output whereas the switching regulator topologies can be designed to move bidirectionally. A bi-directional conversion is useful in regenerative braking of vehicles where power is supplied from wheels during braking. Selection of an appropriate converter topology is an important part of designing the systems as the converter plays a major role in determining the overall performance of the system. Based on an area of application, a suitable converter can be proposed. This paper presents different topologies of DC-DC converters used in various applications with reduced ripple by MATLAB SIMULINK software